2008
DOI: 10.1007/s11771-008-0052-5
|View full text |Cite
|
Sign up to set email alerts
|

Penetration grouting reinforcement of sandy gravel

Abstract: To study the relationship between grouting effect and grouting factors, three factors (seven parameters) directionless pressure and small cycle grouting model experiment on sandy gravel was done, which was designed according to uniform design method. And regressing was applied to analysis of the test data. The two models test results indicate that when the diffusing radius of grout changes from 26 to 51 cm, the grouted sandy gravel compressing strength changes from 2.13 to 12.30 MPa; the relationship between d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Scholars have employed the permeation column test method to inject grout into a stratum, analyzed the influence of grout on the stratum, and explored grout injectability ( 11 ). Among these scholars, Yang et al adopted the uniform design method and studied the relationship between the grouting effect and grouting factor ( 12 ). The researchers concluded that the gravel porosity, gravel permeability coefficient, grouting pressure, grouting time, and water–cement ratio were the main factors influencing the grouting effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Scholars have employed the permeation column test method to inject grout into a stratum, analyzed the influence of grout on the stratum, and explored grout injectability ( 11 ). Among these scholars, Yang et al adopted the uniform design method and studied the relationship between the grouting effect and grouting factor ( 12 ). The researchers concluded that the gravel porosity, gravel permeability coefficient, grouting pressure, grouting time, and water–cement ratio were the main factors influencing the grouting effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…At the same time, grouted curtains prevent the inrush of water and mud by water channels be plugged (Xue et al, 2021), and effective grouting is very important for ensuring the construction safety. Nevertheless, the grouting effect is influenced by many factors, such as water cement ratio, permeability coefficient, grouting pressure and grouting time (Yang et al, 2008). Zheng et al (2020) analyzed the flowing regularity of grout spreading against flowing groundwater and fluid pressure distribution in a grouting work, and proposed a criterion for risk assessment on overburden stratum uplifting.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, many studies have been carried out to find the penetration grouting diffusion laws of grouting fluids in the injected medium. As early as 1938, Maag studied the penetration diffusion law of Newtonian fluid in isotropic homogeneous medium [2]; Zou analyzed the columnar penetration grouting diffusion radius expression for Newtonian fluid [4]; Uddin, Yang, and Li et al studied the penetration diffusion mechanism of Newton, Bingham, and power-law fluids in sandy stratum [5][6][7][8]; Ye et al discussed the penetration diffusion mechanism and model based on Newtonian fluid, Bingham fluid, and power-law fluid for shield tunnel grouting [9][10][11]; Dayakar and Yang analyzed the penetration diffusion law of Bingham fluid in gravel soil layers [12,13]; Draganovic and Fang et al studied the penetration grouting diffusion law considering the percolation effect [14][15][16]; Tiruoatl, Bolisetti, and Sui et al explored the penetration grouting mechanism of chemical grout in porous media [17][18][19]; Zhou et al analyzed the penetration diffusion model considering the tortuosity effect [20]; Zhang et al explored the penetration grouting diffusion law of quick-setting cement in porous media [21]; Yang et al explored the penetration diffusion laws and mechanisms for Newtonian fluid, Bingham fluid and power-law fluid in the injected media, which were verified by the grouting experiments [22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%